Is group-based physical therapy superior to individual rehabilitation in elderly adults after total knee arthroplasty? A prospective observational study - Julian Krumov; Vasil Obretenov; Hristo Bozov; Nedelcho Tzachev; Hristina Milanova; Kiril Panayotov; Jannis Papathanasiou (PAGEPress Publications, 2022)
Knee osteoarthritis (OA) is the most prevalent joint disease and one of the leading causes of disability, poor physical activity levels (PAL), and quality of life (Qol) of elderly people worldwide. The purpose of this study was to evaluate the superiority of a novel group-based physical therapy (GBPT) intervention compared to a more traditional one-to-one individual physical therapy (IPT) among elderly Bulgarian subjects underwent total knee arthroplasty (TKA). One hundred and thirty elderly TKA recipients of both genders with mean age=72.69±0.44 were randomly assigned to GBPT or to one-to-one IPT. Elderly participants were assessed at baseline and at 3 and 6 months after both rehabilitation interventions, with the use of the following evaluation tools: Physical Activity Scale for the Elderly (PASE), Six-Minute Walk Test (6MWT), and Short Form Health Survey questionnaire (SF-36v2). At 6 months elderly TKA recipients who received GBPT achieved 7.36 points more in the PASE questionnaire when compared with the IPT group. Elderly participants of the GBPT group walked significantly longer distance during the 6MWT than TKA recipients attended IPT, respectively 421.56 m vs. 398.62 m, (p< 0.001). Furthermore, significantly greater improvement in health-related quality of life (HRQoL) was obtained from the elderly participants of the GBPT arm compared with the participants of the IPT arm, respectively 70, 7% vs. 60, 8% at 6 months follow up. We conclude that our results suggest the superiority of the GBPT in terms of PAL (PASE score, 6MWT) and HRQoL among elderly TKA recipients across the first 6 months.